NATIONAL AND INTERNATIONAL HUMAN RIGHTS OF OLDER PERSONS INDEX (IOPHRI). (11th November 2018) - Doron, I; Cox, C; Spanier, B; Giannaraki, E
Abstract: Composite indicators are increasingly used by statistical offices and national or international organizations to convey and compare information on the status of countries, states and provinces. In specific, within the field of aging and older persons, over the last two decades, several international indices were developed in the field of well-being of older persons. In 2017, Doron and Spanier presented for the first time a conceptual framework for a new index of human rights of older persons (the IOPHRI). However, this new index has not been tested or applied in order to examine its ability to contribute to the actual measurement and assessment of the human rights of older persons. In this presentation, the comparative international findings of the implementation of the IOPHRI to six countries will be presented: USA, Australia, Chile, Israel, India, and Ireland. The findings contribute to the further development of measuring the human rights of older persons in two aspects: First, on the methodological level, the findings reveal the challenges involved in comparing different legal systems and "weighing" human rights. Second, on the substantive level, the findings reveal how forma legal human rights of older persons are more connected to legal cultures and histories than to the actual real life experiences of older persons.